SEP-like genes of Gossypium hirsutum promote flowering via targeting different loci in a concentration-dependent manner - Chen, Liting; Yan, Yuanyuan; Ke, Huifeng; Zhang, Zihao; Meng, Chengsheng; Ma, Limei; Sun, Zhengwen; Chen, Bin; Liu, Zhengwen; Wang, Guoning; Yang, Jun; Wu, Jinhua; et al. (Frontiers in Plant Science, 2022)
SEP genes are famous for their function in the morphological novelty of bisexual flowers. Although the diverse functions of SEP genes were reported, only the regulatory mechanisms underlying floral organ development have been addressed. In this study, we identified SEP-like genes in Gossypium and found that SEP3 genes were duplicated in diploid cotton varieties. GhSEP4.1 and GhSEP4.2 were abundantly transcribed in the shoot apical meristem (SAM), but only GhSEP4.2 was expressed in the leaf vasculature. The expression pattern of GhSEPs in floral organs was conserved with that of homologs in Arabidopsis, except for GhSEP2 that was preponderantly expressed in ovules and fibers. The overexpression and silencing of each single GhSEP gene suggested their distinct role in promoting flowering via direct binding to GhAP1 and GhLFY genomic regions. The curly leaf and floral defects in overexpression lines with a higher expression of GhSEP genes revealed the concentration-dependent target gene regulation of GhSEP proteins. Moreover, GhSEP proteins were able to dimerize and interact with flowering time regulators. Together, our results suggest the dominant role of GhSEP4.2 in leaves to promote flowering via GhAP1-A04, and differently accumulated GhSEP proteins in the SAM alternately participate in forming the dynamic tetramer complexes to target at the different loci of GhAP1 and GhLFY to maintain reproductive growth. The regulatory roles of cotton SEP genes reveal their conserved and diversified functions.